2018
DOI: 10.3991/ijet.v13i11.9600
|View full text |Cite
|
Sign up to set email alerts
|

Design of Heterogeneous Data Exchange Technology for Teaching Resources Based on ICMPv6

Abstract: To promote the innovation of teaching resources and heterogeneous data exchange platform technologies and theories, heterogeneous data exchange platforms based on ICMPv6 teaching resources were studied. First, based on ICMPv6, the middle-tier architecture of the heterogeneous data exchange platform for teaching resources was studied. Second, the application layer architecture in the heterogeneous data exchange platform system of educational resources was studied. The middle layer and application layer were des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…The reasons underlied this rational description are the instructional model cognitive strategies based involved interactive components which consist of :assessing higher order thinking abilities of the students before participating the cognitive strategies based instructional approach , deciding instructional goals, deciding students' learning achievement, deciding instructional strategies, deciding instructional materials, deciding instructional evaluation , and deciding instructional feed back as shown in figure 2. All of them are the reflection of synthesized of the theories and research results which have been described previously.The research finding dealing with the intructional model which involves interactive componens are also supported by Suardana [48] and Wei Fang [49] VI. CONCLUSION In accordance to the research results, it is concluded that cognitive strategies based instructional model is effective for improving higher order thinking of the students with cognitive expressing difficulties.…”
Section: Discussionmentioning
confidence: 65%
“…The reasons underlied this rational description are the instructional model cognitive strategies based involved interactive components which consist of :assessing higher order thinking abilities of the students before participating the cognitive strategies based instructional approach , deciding instructional goals, deciding students' learning achievement, deciding instructional strategies, deciding instructional materials, deciding instructional evaluation , and deciding instructional feed back as shown in figure 2. All of them are the reflection of synthesized of the theories and research results which have been described previously.The research finding dealing with the intructional model which involves interactive componens are also supported by Suardana [48] and Wei Fang [49] VI. CONCLUSION In accordance to the research results, it is concluded that cognitive strategies based instructional model is effective for improving higher order thinking of the students with cognitive expressing difficulties.…”
Section: Discussionmentioning
confidence: 65%